Future Business Software Current Trends in Business Software Development - Brunetti, Gino; Feld, Thomas; Heuser, Lutz; Schnitter, Joachim; Webel, Christian (Progress in IS, 2014)
What will business software look like in the future? And how will it be developed? This book covers the proceedings of the first international conference on Future Business Software - a new think tank discussing the trends in enterprise software with speakers from Europe's most successful software companies and the leading research institutions. The articles focus on two of the most prominent trends in the field: emergent software and agile development processes. "Emergent Software" is a new paradigm of software development that addresses the highly complex requirements of tomorrow's business software and aims at dynamically and flexibly combining a business software solution's different components in order to fulfill customers' needs with a minimum of effort. Agile development processes are the response of software technology to the implementation of diverse and rapidly changing software requirements. A major focus is on the minimization of project risks, e.g. through short, iterative development cycles, test-driven development and an intensive culture of communication.